2014 8th. Malaysian Software Engineering Conference (MySEC) 2014
DOI: 10.1109/mysec.2014.6986021
|View full text |Cite
|
Sign up to set email alerts
|

Agile transformation: What is it about?

Abstract: Agile software development by offering new values motivates software companies to use Agile methods instead of traditional methods. However, reviewing the literature shows that leaving traditional methods and moving to Agile methods is subjected to many serious challenges. We have conducted a large-scale research study to empirically discover various aspects of Agile transformation. Our Grounded Theory study showed the general outline of Agile transformation. The main aim of this paper is to figure out the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…Before the transformation is started, several publications recommend having a defined objective and reasons for change . There is a need for a motivation in order to perform a transformation .…”
Section: Resultsmentioning
confidence: 99%
“…Before the transformation is started, several publications recommend having a defined objective and reasons for change . There is a need for a motivation in order to perform a transformation .…”
Section: Resultsmentioning
confidence: 99%
“…This study aimed to find the all aspects of transformation to Agile and their related realities [19]. Data analysis showed that the transition process is strongly influenced by customers.…”
Section: Resultsmentioning
confidence: 99%
“…This paper only describes the explored transition facilitators. Interested readers are referred to the [17,18,[20][21][22][23] which have covered various aspects of the transition process as results of the current Grounded Theory study. …”
Section: Theory Generationmentioning
confidence: 99%